Determinants of Deposit-Insurance Adoption and Design - Demirgüç-Kunt, Asli; Kane, Edward J.; Laeven, Luc (World Bank, Washington, DC, 2012)
The authors seek to identify factors that influence decisions about a country's financial safety net, using a new dataset on 170 countries covering the 1960-2003 period. Specifically, they focus on how outside influences, economic development, crisis pressures, and political institutions affect deposit insurance adoption and design. Controlling for the influence of economic characteristics and events such as macroeconomic shocks, occurrence and severity of crises, and institutional development, they find that pressure to emulate developed-country regulatory frameworks and power-sharing political institutions dispose a country toward adopting design features that inadequately control risk-shifting.